KISAH DAUD A.S DALAM PERSPEKTIF AL-QUR’AN - Muhammad, Muhammad Thaib (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2018)
The story of David a.s. in the history of the religious world is a very important one, because all the religions of the world recognize that David a.s is descended from Ya'qub a.s descendant of his son Yahuza. Allah Almighty has made him a prophet and a king. The Bible scholars have mentioned it in the Bible and in the Bible. God has revealed the book of Psalms as a guide in carrying out his preaching. Allah believes in the Qur'an: